Genetic Diversity of Blumeria graminis f. sp. hordei in Central Europe and Its Comparison with Australian Population - Komínková, Eva; Dreiseitl, Antonín; Malečková, Eva; Doležel, Jaroslav; Valárik, Miroslav (PloS one, 2016)
Population surveys of Blumeria graminis f. sp. hordei (Bgh), a causal agent of more than 50% of barley fungal infections in the Czech Republic, have been traditionally based on virulence tests, at times supplemented with non-specific Restriction fragment length polymorphism or Random amplified polymorphic DNA markers. A genomic sequence of Bgh, which has become available recently, enables identification of potential markers suitable for population genetics studies. Two major strategies relying on transposable elements and microsatellites were employed in this work to develop a set of Repeat junction markers, Single sequence repeat and Single nucleotide polymorphism markers. A resolution power of the new panel of markers comprising 33 polymorphisms was demonstrated by a phylogenetic analysis of 158 Bgh isolates. A core set of 97 Czech isolates was compared to a set 50 Australian isolates on the background of 11 diverse isolates collected throughout the world. 73.2% of Czech isolates were found to be genetically unique. An extreme diversity of this collection was in strong contrast with the uniformity of the Australian one. This work paves the way for studies of population structure and dynamics based on genetic variability among different Bgh isolates originating from geographically limited regions.
Keywords: Australia; Czech Republic; Austrálie; technika náhodné amplifikace polymorfní DNA; Phylogeny; DNA, Fungal; DNA fungální; fylogeneze; Polymorphism, Genetic; Ascomycota; Česká republika; polymorfismus genetický; Random Amplified Polymorphic DNA Technique